Evolving U.S. monetary policy and the decline of inflation predictability - Luca Benati; Paolo Surico (European Central Bank (ECB), 2007)
Using a structural VAR with time-varying parameters and stochastic volatility on post-WWII U.S. data, we document a striking negative correlation between the evolution of the long-run coefficient on inflation in the monetary rule and the evolution of the persistence and predictability of inflation relative to a trend component. Using a standard sticky-price model, we show that a more aggressive policy stance towards inflation causes a decline in inflation predictability, providing a possible interpretation for the findings of the structural VAR.
Keywords: E37; E52; E58; 330; Bayesian time-varying VARs; frequency domain; Great Inflation; predictability; sign restrictions; Inflationsbekämpfung; Regelbindung versus Diskretion; Inflation; Prognoseverfahren; VAR-Modell; Dynamisches Gleichgewicht; Stochastischer Prozess; USA